Marketing Adaptation Strategy of The One Legian Hotel To Changes in Demographics of Indian Tourist Visits - Purnama Dewi, Desak Made; Pratiwi, Ida Ayu Putu Wismahari; Dewi, Ni Putu Adellia Puspita; Wijaya, Gede Wiradharma Andika; Ariana, I Putu Nova Tulus (Jurnal Manajemen Pelayanan Hotel, 2024)
This research aims to identify marketing adaptation strategies carried out by The ONE Legian Hotel in facing changes in the demographics of Indian tourist visits. This research uses a qualitative approach with data collection techniques in the form of in-depth interviews and observations related to hotel marketing through the 7P marketing mix analysis technique. The research results show that The ONE Legian Hotel has implemented several marketing adaptation strategies to attract Indian tourists. First, the hotel increases promotions through popular platform online sites in India, such as travel websites and social media. Additionally, they also collaborate with local travel agents in India to expand their marketing network. The hotel also adapts the product offerings according to the needs and preferences of Indian tourists, such as providing a vegetarian menu. With the characteristics of Indian guests who tend to be careful in spending and have high expectations, this hotel offers competitive prices and attentive service to avoid complaints. In addition, there are also changes in trends and preferences of Indian tourists that hotels need to continuously monitor and respond to. Thus, this research provides valuable insights for the hospitality industry, especially for hotels seeking to adapt their marketing strategies to the changing demographics of Indian tourist visits. The practical implication of this research is the importance of continuously monitoring and adapting marketing strategies according to changing market needs and preferences.